PERPUSTAKAAN ANAK KOTA PONTIANAK - Starling, Deveny; Purnomo, Yudi; Irwin, Irwin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2020)
The issue of low literacy culture and reading interest in Pontianak City can be overcome by introducing children a culture of literacy and reading interest from an early age. Provision of special library facilities for children that can accommodate children's reading and learning activities in accordance with their characters and needs is needed to improve literacy culture and reading needs of children. However, until now children’s library has not been available in Pontianak. Children's library is a library that is devoted to accommodating children's learning activities that are adjusted again to meet the special needs of children The activities in the children's library are educative learning and play activities and the provision of children's services as supporting activities. The design of the Pontianak City Children's Library is located on Ahmad Yani street. The design concepts are processed with colors and shapes on the building facade, the provision of a natural environment in the form of a garden and inner courtyard as well as the concept of indoor layout using an open plan system. This design process aims to create a children's library that expresses a conducive, imaginative and creative atmosphere that is appropriate to the characteristics of the child.